Peningkatan Pengelolaan Keuangan UMKM melalui Workshop Penyusunan Laporan Keuangan untuk Mendukung Pertumbuhan Ekonomi - Dwi Handarini; Septi Nurmalita; Diah Armeliza; Adam Zakaria; Vanesa Amalia Duati; Fakhri Salman Alparisi (Politeknik Piksi Ganesha Indonesia, 2026)
This community service program aims to improve the ability of Micro, Small, and Medium Enterprises (MSMEs) to prepare simple financial statements and understand the importance of business legality through simple technology-based training. The program was conducted in Rawamangun, East Jakarta, involving young entrepreneur partners such as Cdj Gallery, Fisy Tee, Wrappedinlove.idn, Aroma Kue, Dough and HA, Nyameal Ajaa, and SMK Sahid Jakarta Pastry & Bakery. The main challenges faced by the partners included low financial literacy, the mixing of personal and business finances, and limited use of digital financial recording. The program was implemented through five stages: socialization, financial statement preparation training, implementation of a simple financial statement template, mentoring, and evaluation. A participatory approach involved participants in transaction recording, income statement preparation, and simulations of obtaining a Business Identification Number (NIB) through the Online Single Submission (OSS) system. Evaluation results showed improved understanding of basic accounting principles and awareness of business legality.